Hand eczema among healthcare professionals in the Netherlands: prevalence, absenteeism, and presenteeism. (28th June 2013) - van der Meer, Esther W. C.; Boot, Cécile R. L.; van der Gulden, Joost W. J.; Jungbauer, Frank H. W.; Coenraads, Pieter Jan; Anema, Johannes R.
Abstract Background Healthcare professionals have a high risk of developing hand eczema. Hand eczema can interfere with their work. Objectives To investigate the prevalence of self‐reported hand eczema among healthcare professionals in the Netherlands, and to investigate absenteeism and presenteeism resulting from hand eczema. Methods A questionnaire‐based observational study was performed. Participants were recruited from hospitals and nursing homes in the Netherlands. The study population consisted of 1232 healthcare professionals. We used the NOSQ‐2002 to measure hand eczema and the PRODISQ for absenteeism and presenteeism. Results The 1‐year prevalence of hand eczema among healthcare professionals was 12%. Among all participants, 47% reported symptoms related to hand eczema. Sick leave resulting from hand eczema was reported by 0.3% of healthcare professionals in general, and by 1.7% of healthcare professionals with hand eczema. In the group with hand eczema, 3.1% reported a large effect on presenteeism. Conclusions The 1‐year prevalence of hand eczema among healthcare professionals in the Netherlands is low, but the prevalence of symptoms related to hand eczema is quite high. Hand eczema seems to have little impact on work in terms of absenteeism and presenteeism.